Interação mãe-bebê: indicadores de habilidade comunicativa intencional em contextos de brincadeira - Costa, Ana Cristina Ramos (2018)
The present research investigates the intentional communication of infants interacting with their mothers, specifically in free play contexts. Researches point out that this situation favors the occurrence of mediations that may contribute to the development of typically human abilities, such as the ability to communicate intentionally. This study started from the cultural-historical framework of Vigotsky that defends the role of social interaction and culture as primordial elements for human development. We have also resorted to contemporary research that investigates the ability of intentional communication, one of the pillars of child social cognition and the development of language, a skill that emerges in children's early years. In this direction the main objective of this research was to analyze the modalities of games and indicators of ability of intentional communication during situations of play. Six motherinfant dyads of nine, twelve and fifteen months of age participated in this study. The instruments used in this research were a sociodemographic questionnaire, a semistructured interview applied to the mothers, a video camera, audio recorder, pencil and paper for the recording and transcription of the interactive episodes. The analysis of the interview material with the mothers indicated in general that they perceive the development of their children as satisfactory and define them as smart and intelligent. Regarding the conceptions of the mothers about the games of their babies, it was reported that in different stages of development, their children engaged in different types of games: at nine months they reported more exploratory games and at fifteen months the games involved interaction with each other and the handling of toys in a conventional way. Concerning the analysis of videotaped interactions, it was noticed that all the interactive episodes presented dyadic and triadic engagements and specifically at fifteen months, an episode of collaborative engagement. The analysis of the prank episodes allowed to identify, at nine months, intentional communicative acts of the babies, such as, staring at the mother, accompanying the movements that the mother performs with the object and dancing. Already at twelve months there was an intentional gesture of picking up the toy from the mother's hand, vocalizing and halffinal behavior in the use of toys by the babies of that age. At fifteen months it was observed that all episodes of conventional play included intentional communicative acts of pointing with vocalization and verbalizations during the handling of the toys. The results of the present study emphasize the mediating role that adults play in the development of sociocognitive and linguistic skills, especially in episodes of joint play, an activity that characterizes childhood and can contribute to overall child development. It is also worth mentioning the contribution of this research in the sense of producing reflections and empirical data that can support preventive programs of intervention of psychologists and other professionals who work in educational and health contexts aiming at the promotion of human development and the early identification of damages in the communication and oral language.